Implementation of an Exclusive Concept in the Gallery Showroom & Typical Surabaya Batik Making Training - Anitu, Maria Ratih; Poedjioetami, Esty; Azizah, Siti (Journal of Civil Engineering, Planning and Design, 2024)
One of the Surabaya government's efforts to preserve history and culture is to maintain the local batik industry. Surabaya batik designs have a strong and bold color concept. This Surabaya batik motif is inspired by the local area. Facilities to facilitate the development of typical Surabaya batik motifs can be said to be very minimal, for this reason the provision of facilities in the form of a Training Center and Gallery for Typical Surabaya Batik, as a medium for preserving and developing the creativity of typical Surabaya batik is very necessary. This design uses descriptive qualitative research with a scientific background of phenomena that occur in the field, through the process of collecting data from literature studies and field studies which are analyzed in detail and then explained descriptively, so that they can be used as a reference in designing the intended facilities. The design of the Surabaya Typical Batik Training Center and Gallery has an exclusive space concept, namely specializing Surabaya batik to be enjoyed in a luxurious room atmosphere and varied spatial experiences so that the space is not monotonous and makes Surabaya batik motifs a strong and bold design characteristic in that space.